KOTA LAMA SEMARANG SITUS SEJARAH YANG TERPINGGIRKAN - Ika Dewi Retno Sari (Berkala Arkeologi, 2012)
The existence of Semarang city as a trading town on the north coast of Java had been going on since the founding of Old Mataram Kingdom and continues to grow, until the period of Dutch colonial rule. The rapid development as a city of Semarang in the Dutch colonial period was marked by the establishment of the buildings at the site which is now called Semarang Old Town. Most of these buildings serve as offices and private VOC trade. Over time, Semarang became not only a trading center but it evolved into a gemeente (municipality), up to the present period. Nevertheless, there seems to be lack of interest in making the history of Semarang as a subject in teaching history at the local level, especially in educational circles, as the subject matter in teaching history. As a source of considerable historical importance, there is nothing wrong if a teacher of History, especially in the city of Semarang, making the Old City as a source of learning for students in the city of Semarang. Therefore the existence of sites as well as historical buildings in the city of Semarang is should no longer simply regarded as old buildings that have without meaning. And at least it will foster public awareness of Semarang city, especially among students to participate in regard to keep the existence of the Old Town and make it as an asset of History and Tourism in the city of Semarang.